„Ad honorem celsitudinemque Dei omnipotentis” – sposoby rehabilitowania astrologii w twórczości mistrzów krakowskich epoki przedkopernikańskiej - Konarska Zimnicka, Sylwia (Saeculum Christianum. Pismo Historyczne, 2019)
Astrology in the Middle Ages aroused a lot of controversy, especially in its predictive version. The Church criticized astrologers who, relying on the celestial bodies, tried to predict the future. This superstitious astrology cast a bad light on the natural astrology, which was tolerated and even accepted. This acceptance was expressed in many ways by Cracow masters. In their astronomical and astrological works they tried to prove that astrology was not in opposition to Christianity.